Interdisciplinary research : process and theory - Repko, Allen F.; Szostak, Rick, 1959- (Thousand Oaks, California : Sage, 2026)
"The fifth edition of Interdisciplinary Research: Process and Theory reflects the substantial research on all aspects of interdisciplinarity published since the fourth edition in 2020. The literature on interdisciplinary research continues to expand; in this revision, we have drawn on many works from Europe, Asia, Australia, as well as North America. This book also reflects feedback from faculty and students who have used the earlier editions. Our goal is to provide a comprehensive and systematic presentation of the interdisciplinary research process and the theory that informs it, not only for students, but also for professionals and interdisciplinary teams. The book emphasizes the relationships between theory, research, and practice in an orderly framework so that the reader can more easily understand the nature of the interdisciplinary research process"-- Provided by publisher.
Includes bibliographical references and index.
Texto en inglés.
Keywords: Interdisciplinary research